Reducing Food Waste During COVID-19: Testing Role Model Stories as a Strategy for Promoting Conservation Behaviors - O’Donnell, Nicole Hummel; Karabas, Ismail; Hill, Aloni (Frontiers in Communication, 2022)
This study investigates how role model stories may inspire food waste reduction during times of scarcity. We conducted a 2x2 between-subjects experiment (N=358, U.S. adults) to test the effectiveness of messages that emphasized role model success (reduced waste/zero-waste) and achievement difficulty (easy/difficult) on intentions to set a personal food waste goal. Exposure to role models who lived a zero-waste lifestyle had a self-deflating effect, as this behavior was viewed as less attainable by participants. Regardless of difficulty framing, exposure to role models who reduced their waste enhanced participants’ perceptions of goal attainability, motivation, and intentions. No interaction effects were found between levels of success and achievement difficulty. Considering covariates, individuals who reported enhanced food waste awareness due to COVID-19 reported higher goal setting intentions. Hence, times of perceived food scarcity may provide an ideal opportunity for promoting food waste reduction and conservation strategies. Results from this study provide guidance for how role model stories can best inspire waste reduction without hindering attainability and motivation. We discuss implications for applying the motivational theory of role modeling in conservation and communication contexts.